2019
DOI: 10.1038/s41598-019-40526-5
|View full text |Cite
|
Sign up to set email alerts
|

Rotatable precipitates change the scale-free to scale dependent statistics in compressed Ti nano-pillars

Abstract: Compressed nano-pillars crackle from moving dislocations, which reduces plastic stability. Crackling noise is characterized by stress drops or strain bursts, which scale over a large region of sizes leading to power law statistics. Here we report that this “classic” behaviour is not valid in Ti-based nanopillars for a counterintuitive reason: we tailor precipitates inside the nano-pillar, which “regulate” the flux of dislocations. It is not because the nano-pillars become too small to sustain large dislocation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 52 publications
3
4
0
Order By: Relevance
“…1 [35]). One may notice that this size scale is close to typical micropillar experiments [9,12,15,23], but here the use of periodic boundaries implies that we are simulating a part of a bulk system. A total of 24 initial dislocations in the slip system 1 2 110 {111} imply an initial dislocation density ρ 0 ≈ 2.0 × 10 12 m −2 .…”
Section: Methodssupporting
confidence: 61%
See 1 more Smart Citation
“…1 [35]). One may notice that this size scale is close to typical micropillar experiments [9,12,15,23], but here the use of periodic boundaries implies that we are simulating a part of a bulk system. A total of 24 initial dislocations in the slip system 1 2 110 {111} imply an initial dislocation density ρ 0 ≈ 2.0 × 10 12 m −2 .…”
Section: Methodssupporting
confidence: 61%
“…These considerations then lead us to the question of how one may, by controlling the precipitate content of a 3D crystal, tune its mechanical properties [12,14,23] and how that relates to the statistical physics aspects-relaxation, burst size distributions-for a given precipitate microstructure. Previous studies [24][25][26][27] have addressed the problem of individual dislocations interacting with precipitates.…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed a much weaker size effect on strength in alloys compared with pure materials. This was interpreted as the fingerprint of a tailored internal length scale, which also suggested the possibility of the reduction of plastic intermittency [119][120][121]. The framework proposed in Section 2.4, and particularly our equations (4) and ( 5), can be used to rationalize these observations.…”
Section: Alloyssupporting
confidence: 52%
“…The mild movements still constitute avalanches in the description of (Salje and Dahmen 2014). Coexistence of mild and wild movements is well known for restructuring processes in many materials under external forcing, like ice (Weiss 2019), martensites (Chen et al 2019), dislocation (Pan et al 2019) and in crack propagation (Bonamy et al 2008;Laurson et al 2010). Mild processes are much more difficult to observe than spiky jerks (Casals et al 2019) where the optical observation of domain wall movements proved particularly useful (Casals et al 2020).…”
Section: Moving Twin Boundariesmentioning
confidence: 99%